2017
DOI: 10.1186/s13568-017-0518-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Methylobacterium oryzae CBMB20 aggregates for salt tolerance and plant growth promoting characteristics for bio-inoculant development

Abstract: Salinity is one of the major factors contributing to the loss of crop productivity and thereby impacting livelihood of people in more than 100 countries of the world and the area of land affected by salinity is increasing day by day. This will worsen due to various factors such as drought that might result in high soil salinity. Use of plant growth promoting rhizobacteria is one of the promising eco-friendly strategies for salinity stress management as part of sustainable agricultural practices. However, it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Several studies have tried to analyze the mechanisms by which bacteria can improve the resistance in plants. Hence, some research shows that the use of PGP bacteria can promote plant growth and enhance salt tolerance capacity by inducing synthesis of osmolytes (Siddikee et al, 2011;Chanratana et al, 2017;Karnwal, 2017;León et al, 2018). Our results revealed that after evaluation, we selected Acinetobacter sp.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Several studies have tried to analyze the mechanisms by which bacteria can improve the resistance in plants. Hence, some research shows that the use of PGP bacteria can promote plant growth and enhance salt tolerance capacity by inducing synthesis of osmolytes (Siddikee et al, 2011;Chanratana et al, 2017;Karnwal, 2017;León et al, 2018). Our results revealed that after evaluation, we selected Acinetobacter sp.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, it has been demonstrated that salt-tolerant PGP bacteria isolated from alkaline soil, are physiologically adapted to abiotic stresses and could increase salt tolerance capacity and the growth of various crop plants, such as tomato, maize, and pepper in saline soil conditions (Mayak et al, 2004;Ferreira et al, 2018;Yasin et al, 2018). In fact, efficient PGPR used to alleviate NaCl-induced stress must be obligatory resistant to this constraint, or their development will be inhibited by salt (Sharma et al, 2015;Upadhyay and Singh, 2015;Chanratana et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, different members of the Methylobacterium genus produce high levels of CKs and increase the tolerance of plants to abiotic stresses (e.g. salt and drought stress) ( Knief et al, 2012 ; Lee et al, 2015 ; Chanratana et al, 2017 ; Jorge et al, 2019 ).…”
Section: Plant-associated Microbial Communitiesmentioning
confidence: 99%
“…M. nodulans Crotalaria providing nitrogen; decreasing levels of ethylene [12,16,17] M. oryzae Rice increasing plant cytokinin levels; solubilizing phosphate [13,[18][19][20] M. extorquens Pine; Arabidopsis; Brassia inducing the expression of host defense genes [21,22] M. mesophilicum Sugarcane increasing plant cytokinin levels [23] M. radiotolerans Brassia; Combretaceae providing nitrogen; exhibited high antibacterial and antifungal activity; decreasing levels of ethylene [24,25] M. populi Brassia providing nitrogen [26] M. komagatae Brassia providing nitrogen [17] M. aquaticum Brassia providing nitrogen [17] M. funariae Moss increasing plant cytokinin levels [27] M. phyllosphaerae Rice decreasing levels of ethylene [28]…”
Section: Species Name Host Plants Effects On Host Plantsmentioning
confidence: 99%